Expression of ephrinA5 during development and potential involvement in the guidance of the mesostriatal pathway - Deschamps, C.; Faideau, M.; Jaber, M.; Gaillard, A.; Prestoz, L. (Experimental neurology, 2009)
Identifying guidance cues that direct axon growth to their final connections during development is of crucial interest if we aim to repair circuits damaged in adulthood following neurodegenerative disorders or common traumatic injuries. In this work, we set out to determine the ephrinA5 guidance molecule involvement in the establishment of the mouse mesostriatal pathway during development. We showed, in vitro and in vivo, that a proportion of mesencephalic dopaminergic cells express the ephrinA5 receptor, EphA5. Moreover, we observed, using stripe assays, that ephrinA5 purified protein has a repulsive effect on most of the mesencephalic dopaminergic projections. In vivo, we detected rostro-caudal and ventro-dorsal ephrinA5 protein expression gradients in the vicinity of the dopaminergic axons in the ventral telencephalon and in the striatum, during the embryonic and early postnatal development. In addition, other EphA5 ligands were also detected in the mesostriatal pathway. Together, these expression patterns suggest that, ephrinAs and more specifically ephrinA5, may be actors in the guidance of dopaminergic projections. Further studies will focus on identifying the molecular specificity of these guidance cues, taking into account the mesencephalic dopaminergic heterogeneous neuronal population. This may help increase the integration of neuronal transplants in the mature lesioned brain or provide tools to re-establish mesostriatal circuits in vivo.